2013
DOI: 10.1002/qj.2214
|View full text |Cite
|
Sign up to set email alerts
|

An a priori study of the subfilter‐scale conservation equations for the stably stratified atmospheric surface layer

Abstract: We perform an a priori analysis of the subfilter-scale (SFS) conservation equations for the stably stratified atmospheric boundary layer (ABL). Using data from the Horizontal Array Turbulence Studies (HATS) experiment, we build on previous studies by exploring in greater detail the scale dependence of the mean and root-mean-square (r.m.s.) values of the production terms in the SFS stress and flux budgets. Our analysis shows production terms that are the dominant generation mechanisms for the SFS stresses and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The analysis is confined to application to a convective boundary layer in this study, whereas the proposed approach is available to other situations including a free atmosphere. Ramachandran andWyngaard (2011, 2014) proposed a second-order turbulent model, which predicted all the components of the second-order subgrid covariance, and found that their model showed better performance than a LES using a eddy-diffusivity closure when compared with the data obtained from the Horizontal Array Turbulence Study (HATS; Horst et al 2004) experiment. Nevertheless, a simple analysis in terms of the length scales would partly provide information for constructing a numerical model on the basis of the eddy-diffusivity closure.…”
Section: Introductionmentioning
confidence: 98%
“…The analysis is confined to application to a convective boundary layer in this study, whereas the proposed approach is available to other situations including a free atmosphere. Ramachandran andWyngaard (2011, 2014) proposed a second-order turbulent model, which predicted all the components of the second-order subgrid covariance, and found that their model showed better performance than a LES using a eddy-diffusivity closure when compared with the data obtained from the Horizontal Array Turbulence Study (HATS; Horst et al 2004) experiment. Nevertheless, a simple analysis in terms of the length scales would partly provide information for constructing a numerical model on the basis of the eddy-diffusivity closure.…”
Section: Introductionmentioning
confidence: 98%